Book presentation: New book on evolution of media: “Human as media. The emancipation of authorship” - COSTEA, Carmen (Annals of Spiru Haret University. Economic Series, 2014)
Over 6,000 years of literary civilisation, there have been perhaps 300 million authors: people capable of communicating their opinion beyond their own physical circles. Now, thanks to the Internet, in the historical blink of an eye, the number of authors has reached two billion people.